A Comparative Analysis of the Socio-Economic Status of the Members of Dairy Co-Operatives and Private Dairies in Rajasthan - Kumar, D.; Kadian, K. S.; Tripathi, A. K.; Roy, A. (Indian Journal of Hill Farming, 2016)
Rajasthan have a large scale presence of both the private dairy and the dairy co-operatives which is providing infrastructural, Marketing and Service support to the potential dairy sector of the state. Rajasthan is selected purposively for the present study. Two districts namely Jaipur and Alwar had been purposively selected out of 13 Tehsils of Jaipur district & out of 11 tehsils of Alwar district, list of all the Tehsils comprising both private Dairy and Dairy co-operative societies has been prepared out of them 2 tehsils from each district i.e. Chomu and Shahpura from Jaipur district and Behror & Tijara from Alwar district were selected randomly. Member of dairy co-operative societies and private dairies were selected by proportionate random sampling method. Thus total 100 members of dairy co-operative societies and 100 members of private dairies were selected. Higher Productivity of milch animals is depends on the higher knowledge and adoption of breeding, feeding, health care and management aspect of the dairy farming practices. Total milk yield in last lactation of crossbred, local cows and buffaloes of the member of private dairy was 1226.86, 914.34 and 1068.98 liters; respectively. While In case of member of dairy co-operatives total milk yield in last lactation of crossbred, local cows and buffaloes was 1326.66, 1133.8 and 1230 liters respectively. Total milk yield in last lactation among the dairy co-operative respondent’s animals was found significantly higher than the private dairies. Average milk yield was found to be significantly higher in case of animals of dairy co-operative respondents than the private dairies at 5 % level of probability. Training, dairy extension services, cattle feed, health care services and other dairy development programmes initiated by dairy co-operatives which led to substantial improvement in the milk production of cooperative animals were found to be the major causes behind this difference.